Resumption of Warfarin After Hospitalization for Lower Gastrointestinal Bleeding and Mortality Benefits. Issue 6 (July 2018) - Patel, Parita; Nigam, Neha; Sengupta, Neil
Abstract : Goals: To evaluate whether resumption of warfarin after hospitalization for lower gastrointestinal bleeding (LGIB) is associated with improved 90-day and 6-month survival. Background: LGIB is a common complication for patients on warfarin. There is limited data to guide clinicians on the optimal management of warfarin following hospitalization for LGIB. Study: We identified patients hospitalized with LGIB while on warfarin using a validated, machine-learning algorithm. Patients were classified as those who had warfarin resumed at discharge and those who did not. Univariate and multivariate Cox proportional hazards were used to determine whether resuming warfarin was associated with improved 90-day and 6-month mortality. Results: In total, 607 patients were admitted with warfarin-associated LGIB. A total of 403 (66.4%) patients had warfarin held at discharge. Discontinuation of warfarin was associated with an increased 90-day and 6-month mortality on univariate analysis [hazard ratio (HR), 2.07, 95% confidence interval (CI), 1.04-4.58, P =0.04; HR, 1.78, 95% CI, 1.02-3.27, P =0.04]. On multivariate regression adjusting for age, comorbidities, and transfusion requirement, only a higher Charlson Index was associated with increased 90-day mortality (HR, 1.18, 95% CI, 1.07-1.29, P =<0.001). At 6 months, only older age was associated with an increased mortality on multivariate regression (HR, 1.02, 95% CI, 1.00-1.05, P =0.02), with no significantly increased mortality risk with holding warfarin (HR, 1.48, 95% CI, 0.84-2.78, P =0.18) Conclusions: There was no association between resumption of warfarin at discharge following hospitalization for LGIB and either 90-day or 6-month mortality on multivariate analysis. Mortality in LGIB was largely driven by age and comorbidities.